Taxiway Pavement Evaluation to Support the Operational of Terminal 2 Juanda Airport - Istiar Istiar; Indrasurya B. Mochtar; Wahyu Herijanto; Catur Arif Prastyanto (Institut Teknologi Sepuluh Nopember, 2017)
The movement of aircraft and passengers at Juanda international airport is increasing every year. In 2012, the air side infrastructure of Juanda airport almost reached the maximum capacity. In other side, PT. Angkasa Pura I as the operator of Juanda airport had planned to revitalize the Juanda airport terminal that located on the south side. This terminal was not operated for 8 years. The pavement of taxiway should be evaluated its strength. The evaluation method compared The Pavement Classification Number (PCN) of taxiway pavement with Aircraft Classification Number (ACN). If PCN value was higher than ACN value, so the taxiway pavement could serve aircraft movements. The pavement of taxiway on Juanda airport evaluated by using software COMFAA. Data input into the software COMFAA was the existing pavement structure and the movement of the aircraft that will to use south side of Juanda Airport Terminal. The scenario 1 result is the exiting pavement should be overlaid 7 inches to support The operational of Terminal 2 Juanda Airport. In other side, scenario 2 result showed that the existing taxiway pavement structure was able to hold the load of aircraft movements over 20 years. The PCN value is 80.2 dan the ACN values are 89.3 in the scenario 1 and 75 in the scenario 2.